Synergies Between Lean Construction and Management of Heritage Structures and Conservation Strategies - A General Overview - Brioso X. (2019)
This work was funded by the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica del Perú (CONCYTEC from its acronym in Spanish), according to the Convenio de Gestión N° 232-2015-FONDECYT. The work was carried out with a collaboration of GETEC and Engineering & Heritage research groups at PUCP.